Situation Report: Hungary, 10 October 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Election of Delegates for the HSWP Congress Not Easy / by Judith Pataki Factions Form in the HSWP before the Party Congress / by Zoltan Barany The First Day of the HSWP Congress / by Judith Pataki The Dramatic but Expected Demise of the HSWP / by Alfred Reisch Hungarian Socialist Party Adopts Statutes and Program and Elects Leadership / by Alfred Reisch The Hungarian Socialist Party: How Old and How New? / by Zoltan Barany Opposition Skeptical of Ruling Party's Break with the Past / by Edith Oltay